Handbook on Decision Making Vol 2: Risk Management in Decision Making - Lu, Jie.; Jain, Lakhmi C.; Zhang, Guangquan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book presents innovative theories, methodologies, and techniques in the field of risk management and decision making. It introduces new research developments and provides a comprehensive image of their potential applications to readers interested in the area. The collection includes: computational intelligence applications in decision making, multi-criteria decision making under risk, risk modelling,forecasting and evaluation, public security and community safety, risk management in supply chain and other business decision making, political risk management and disaster response systems. The book is directed to academic and applied researchers working on risk management, decision making, and management information systems.
Part 1. Decision Making Under Risk -- Part 2. Risk Management In Business Decision Making -- Part 3. Risk Assessment and Response Systems.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).; Operations Research/Decision Theory